Efficient, Compact Mid-Infrared Sources: A Systematic Study of Intracavity Difference-Frequency Generation - Saeed Salimian Rizi; Liam G. K. Flannigan; Alex Chiasson; Tyler Kashak; Daniel Poitras; Chang-Qing Xu (Photonics)
This study presents a compact intracavity difference-frequency generation (DFG) source designed for mid-infrared (mid-IR) applications. By optimizing overlap between the pump and signal beams, we obtained a black-box efficiency (<semantics>ηBB</semantics>) of 3.4% W⁻1 and a maximum DFG output power of 63 mW at a wavelength of 3437 nm for a 50 mm long periodically poled lithium niobate (PPLN) crystal. The mid-IR laser was systematically studied for various PPLN lengths (29 mm, 40 mm, and 50 mm), demonstrating extensive tunability across a range of mid-IR wavelengths. Stability assessments over short-term (2 min) and long-term (2 h) periods were also investigated, showing stability values of 0.91% and 1.08%, respectively. These advancements position our DFG laser as a promising candidate for potential applications in greenhouse gas detection and satellite communication, addressing the growing demand for reliable and efficient mid-IR sources.